Radiopharmacological evaluation of a caspase-3 responsive probe with optimized pharmacokinetics for PET imaging of tumor apoptosis. Issue 18 (25th April 2020) - Wang, Shijie; Gao, Dingyao; Li, Ke; Ye, Siqin; Liu, Qingzhu; Peng, Ying; Lv, Gaochao; Qiu, Ling; Lin, Jianguo
Abstract : A PET imaging probe with optimized pharmacokinetics was designed for real-time monitoring of the activity of caspase-3 in tumors. Abstract : Early evaluation of the therapy efficiency can promote the development of anti-tumor drugs and optimization of the treatment method. Caspase-3 is a key biomarker for early apoptosis. Detection of caspase-3 activity is essential for quick assessment of the curative effect. We have reported a PET probe that could image drug-induced tumor apoptosis in vivo . However, high liver uptake limits its application. In order to optimize the pharmacokinetics of the previous probe, we introduced a hydrophilic peptide sequence to minimize liver uptake. The structure of the new probe was confirmed by mass spectrometry and nuclear magnetic resonance. This probe was able to cross the cell membrane freely and could be converted into a dimer through the condensation reaction of 2-cyano-6-aminobenzothiazole (CBT) and cysteine in response to intracellular activated caspase-3 and glutathione (GSH). The hydrophobic dimers further self-assembled into nanoparticles, which could enhance the probe aggregation in apoptotic tumor tissues. In vivo experiments showed that the tumor uptake of the new probe was higher than that of the previous probe, while the liver uptake of the new probe was significantly reduced. The new probe might be promising in imaging apoptotic tumors with suitable pharmacokinetics.